Reinventing the City through Commoning - Lages, J. (TUR'20 - Technopolitics in Urban Regeneration International Conference, 2020)
Reinventing the city through commoning Growing urbanization and the consequent complexity of urban problems demands profound changes in the way urban commons are designed, produced and managed in contemporary times. The top-down approach of conventional urban planning models does not provide the necessary systemic changes to respond to citizens' needs. In response, combining the expansion of network connectivity, collaborative principles and participatory ethics, bottom-up movements have been organizing themselves to explore a multiplicity of common practices and shared urban spaces that can transform this condition. These practices promote collective intelligence based on experiments in local urban contexts to create places for collaboration, sharing and collective ownership, often under the banner of ‘urban commons’. What opportunities and challenges do these collective actions represent in the development of co-creation and co-management processes of our cities? Can they point to new possible paths within the scope of citizen innovation?